Sensitive detection of SARS-CoV-2 spike protein based on electrochemical impedance spectroscopy of Fe3O4@SiO2–Au/GCE biosensor - Xun-Hai You; Yao Liu; Yan-Yan Li; Bing Zhao; Yong Yang; Rohan Weerasooriya; Xing Chen (Advanced Sensor and Energy Materials, 2023)
Highly contagious COVID-19 disease is caused by a novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which poses a serious threat to global public health. Therefore, the development of a fast and reliable method for the detection of SARS-CoV-2 is an urgent research need. The Fe3O4@SiO2–Au is enriched with a variety of functional groups, which can be used to fabricate a sensitive electrochemical biosensor by biofunctionalization with angiotensin-converting enzyme 2 (ACE2). Accordingly, we developed a novel electrochemical sensor by chemically modifying a glassy carbon electrode (GCE) with Fe3O4@SiO2–Au nanocomposites (hereafter Fe3O4@SiO2–Au/GCE) for the rapid detection of S-protein spiked SARS-CoV-2 by electrochemical impedance spectroscopy (EIS). The new electrochemical sensor has a low limit detection (viz., 4.78 pg/mL) and a wide linear dynamic range (viz., 0.1 ng/mL to 10 μg/mL) for detecting the EIS response signal of S-protein. The robust Fe3O4@SiO2–Au/GCE biosensor has high selectivity, stability, and reproducibility for the detection of S-protein with good recovery of saliva samples.